Demographics and Real Interest Rates: Inspecting the Mechanism - Carlos Viana de Carvalho; Andrea Ferrero; Fernanda Nechio (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2016)
The demographic transition can affect the equilibrium real interest rate through three channels. An increase in longevity - or expectations thereof - puts downward pressure on the real interest rate, as agents build up their savings in anticipation of a longer retirement period. A reduction in the population growth rate has two counteracting effects. On the one hand, capital per-worker rises, thus inducing lower real interest rates through a reduction in the marginal product of capital. On the other hand, the decline in population growth eventually leads to a higher dependency ratio (the fraction of retirees to workers). Because retirees save less than workers, this compositional effect lowers the aggregate savings rate and pushes real rates up. We calibrate a tractable life-cycle model to capture salient features of the demographic transition in developed economies, and find that its overall effect is a reduction of the equilibrium interest rate by at least one and a half percentage points between 1990 and 2014. Demographic trends have important implications for the conduct of monetary policy, especially in light of the zero lower bound on nominal interest rates. Other policies can offset the negative effects of the demographic transition on real rates with different degrees of success.
Keywords: E52; E58; J11; 330; Life expectancy; population growth; demographic transition; real interest rate; monetary policy; zero lower bound; Secular Stagnation